THE MEANING OF THE DAKWAH MESSAGE IN THE YOUTUBE LITTLE GIANTZ EPISODE SETENGAH BIJI KURMA - Mubarokah, Fauza Ni'amatul (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Youtube is one of the social media used in delivering da'wah messages. There are many content creators with various shows, one of which is Islamic children's animation which contains many messages in it. This study discusses the meaning of da'wah messages on Little Giantz Youtube in one of its episodes, namely Half a Date Seed. The meaning of the da'wah message contained in it is seen from the symbolic interactions that occur and the signs that are created in every existing scene and can be interpreted with one of the theories, namely semiotic analysis. The da'wah messages contained are various, including through actions, hadiths and sayings. The meaning of da'wah messages includes moral messages for children, messages in the form of obeying parents' advice, and also moral messages to take social action to fellow human beings.